Elections: Between The Realization Of The People's Will And The Threat Of Oligarchy - Hermawan Prasojo (Faculty of Law, Universitas Jenderal Soedirman, 2023)
General elections are one means to realize the people's will in a democratic country. However, realizing the people's will takes work, one of which is the threat of oligarchy in the political process through elections. This research examines the extent to which the people's will has been realized through existing laws and regulations and how the threat of oligarchy occurs in the political process. This research uses a normative, legislative, and conceptual method. Based on the results of the research, it is found that the election arrangements in the existing laws and regulations have generally supported the realization of the will of the people. However, gaps in the regulation of political party recruitment and political party funding can lead to oligarchic practices. Therefore, further study is needed to find a model for regulating political recruitment and funding of political parties.